Trabalho escravo e reforma agrária: experiências do assentamento luar do sertão (2000 a 2005) - SILVA, Cristiane Moreira da (Universidade Federal do Tocantins, 2023)
The objective of the present work is to make visible the voice of workers who went through slavery and who today are settled in the Luar do Sertão settlement, located in the Northern Region of Tocantins, 30 km from the city of Ananás. We used Oral History as methodology in order to understand the experiences of the workers we interviewed. For a long time people have talked about slave labor, but there are still few academic works that approach the theme, either because of the lack of bibliographic sources or because they don't know how to deal with the facts. It was through interviews and informal conversations that it was possible to get to know what in fact these men went through inside the farms, having to stay there for the fact of having to support their families and for having incurred debts when accepting the job. It is not new that organizations such as the CPT (Pastoral Land Commission) and the CDH (Human Rights Center) have been promoting nongovernmental actions to combat slave labor in Brazil, more specifically in the city of Ananás, located in the Bico do Papagaio. These actions include community garden projects and INCRA lands so that these rescued workers do not return to the slavery system, as was the case in the Luar do Sertão Settlement. These developed projects aim at the inclusion of these workers, who are often excluded by society because they are not literate